Protective Effect of Melatonin on Nonylphenol-Induced Reproductive and Behavioral Disorders in First-Generation Adult Male Rats - Mahsa Tavakoli; Ali Akbar Moghadamnia; Fereshteh Pourabdolhossein; Mohammad Hossein Asghari; Sohrab Kazemi (Behavioural Neurology)
Background and Objective. Nonylphenol (NP), as an environmental pollutant, has adverse effects on the reproductive and nervous systems through disrupting the endocrine system and inducing oxidative stress. This study was aimed at investigating the protective effect of melatonin (MLT) on NP-induced reproductive and behavioral disorders in first-generation adult male rats. Methods. Pregnant Wistar rats were randomly assigned into five groups: control, NP (25 mg/kg), NP (25 mg/kg)+MLT (10 mg/kg), NP (25 mg/kg)+MLT (20 mg/kg), and MLT (20 mg/kg). The duration of treatment was 21 days from gestation time. Morris water maze was used to assess learning and memory. NP concentrations of serum and testicular tissue were measured by HPLC. Histological analysis of testicular tissues was done by H&E staining. Results. Behavioral study showed that NP does not impair learning and memory in first-generation rats. Histomorphometric results showed that NP can significantly reduce the cross-sectional area of the seminiferous tubules and the epithelium, the diameter and number of seminiferous tubules, the thickness of the epithelium, and the number of spermatocytes and spermatogonia compared to other groups. MLT reversed the NP-induced histomorphometric. Also, it changes and increased the activity of superoxide dismutase (SOD), total antioxidant capacity (TAC), and catalase (CAT). The level of malondialdehyde (MDA) significantly decreased in MLT-treated groups compared with the NP group. Conclusion. Our finding showed that MLT enhanced the learning process and reduced NP-induced testicular tissue damage through its antioxidants and cytoprotective effects.